FORUM KRITIKA: THE SOUTH AFRICAN NOVEL IN TRANSITION: 1990-2010: COETZEE IN AND OUT OF CAPE TOWN. - Coovadia, Imraan (Kritika Kultura, 2012)
This paper is an attempt to see J.M. Coetzee's emigration from South Africa to Australia as a logical step within his career, and to understand Coetzee's relationship with the city and university of Cape Town. It also tries to set out the nature of Coetzee's self-assertion and self- canonization, and the interplay between Coetzee and the Coetzeean critics.